A Wholistic Approach to Non-Pharmacological Intervention for Primary Dysmenorrhea - Wal, Pranay; Gupta, Divyanshi; Wal, Ankita; Pandey, Shiv S.; Krishnan, Karthickeyan (Current Women's Health Reviews, 2024)
Background: Primary dysmenorrhea is a prevalent complaint among women nowadays. Primary dysmenorrhea is a painful disorder that occurs during the menstrual cycle. It is described as unpleasant menstrual cramps or period discomfort that occurs without the presence of any pelvic illness. Primary dysmenorrhea is one of the most common causes of absence from school, work, and social activities. It has an impact on women's daily quality of life. Objective: To investigate the efficacy and safety of non-pharmacological treatments for women suffering from primary dysmenorrhea. Methods: We looked up information on gynaecology in the Cochrane library, PubMed, ScienceDirect, and other databases. We looked at multiple clinical trial databases from the year before as well as systematic reviews that had been done before. Results: As per qualitative assessment, non-pharmacological management for primary dysmenorrhea is extremely effective and wonderful for overall health. Primary dysmenorrhea can be treated with any of the approaches outlined in this study. Conclusion: The study revealed that non-pharmacological approaches, such as yoga, physical activity, heat treatment, massage therapy, water therapy, dietary supplements, acupressure, aromatherapy, massage therapy, and other non-invasive techniques, have a significant role in the management of dysmenorrhoea. It was observed that women who engage in regular physical activity do not experience severe dysmenorrhea. Additionally, it was discovered in this study that dietary nutrients like vitamin D and other nutraceuticals ameliorate the symptoms of dysmenorrhea.
Keywords: blood supply